2017
DOI: 10.2175/106143017x15023776270214
|View full text |Cite
|
Sign up to set email alerts
|

Physico‐Chemical Processes

Abstract: This review is on the research literature published in 2016 related to the physico-chemical processes for water and wastewater treatment. The review is divided into granular and membrane filtration, sedimentation, coagulation/flocculation, flotation, oxidation, and adsorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 77 publications
(79 reference statements)
0
8
0
Order By: Relevance
“…Ionic hydrogel-based materials are well-known for their potential applications in drugs/dyes-adsorption and wastewater treatment. , To explore such possibilities for this cationic G3 hydrogel, we examined its removal efficiency toward EB dye and SZ drug via UV–vis spectroscopy. The result showed that the absorbances at λ max,EB = 520 nm and λ max,SZ = 359 nm for EB and SZ, respectively, decreased drastically within 24 h, as could be seen clearly from the UV–vis spectra of the supernatant dye solutions before and after charging with G3 (Figure A,B).…”
Section: Resultsmentioning
confidence: 99%
“…Ionic hydrogel-based materials are well-known for their potential applications in drugs/dyes-adsorption and wastewater treatment. , To explore such possibilities for this cationic G3 hydrogel, we examined its removal efficiency toward EB dye and SZ drug via UV–vis spectroscopy. The result showed that the absorbances at λ max,EB = 520 nm and λ max,SZ = 359 nm for EB and SZ, respectively, decreased drastically within 24 h, as could be seen clearly from the UV–vis spectra of the supernatant dye solutions before and after charging with G3 (Figure A,B).…”
Section: Resultsmentioning
confidence: 99%
“…[ 92 ] To solve this crisis, a variety of membrane separation technologies, such as ultrafiltration, [ 93‐94 ] nanofiltration, [ 95‐96 ] membrane distillation, [ 97 ] reverse osmosis, [ 98 ] and reverse osmosis [ 99 ] have been developed and are widely used for desalination of seawater and recycling of polluted water. [ 100‐101 ] Membrane separation technology has been proven to be a safe, energy‐saving and environmentally sustainable method. Due to structural advantages, ultra‐thin MOF/COF membranes are expected to become the next generation liquid separation membranes with high permeability and selectivity.…”
Section: Application Of 2d Mofs/cofsmentioning
confidence: 99%
“…The uptake of various species was studied to assess the potential of the hydrogels for environmental applications (e.g., waste water purification [41][42][43][44][45][46][47]) or biomedical applications (e.g., wound dressings [3,[48][49][50][51][52]).…”
Section: Uptake and Release Of Species From Hydrogelsmentioning
confidence: 99%